ENVIRONMENTAL DISCLOSURE IN LOCAL GOVERNMENT FINANCIAL REPORTS: A SYSTEMATIC LITERATURE REVIEW - Firdaus, Anhar; Arifai, Muhammad; Mariana, Mariana; Fahira, Annisa; Silvia, Intan; Azaria, Putri Syaikah; Azzahra, Rahma (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to analyze the factors influencing the quality and disclosure level of local government financial statements as well as environmental accounting practices in the public sector. The research employs a Systematic Literature Review (SLR) method by reviewing 30 national and international scholarly articles from 2012 to 2024 sourced from databases such as DOAJ, Sinta, and Google Scholar. The findings reveal that the quality of financial statements is affected by human resource capacity, information technology utilization, and internal control systems. Meanwhile, environmental disclosure tends to improve with the adoption of green accounting, strengthened environmental ethics, and increasing public accountability demands. Furthermore, transparent and accountable financial reporting contributes to sustainable governance.